2014
DOI: 10.1371/journal.pone.0081542
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analyses of a Sterol Carrier Protein in Spodoptera litura

Abstract: BackgroundsIn insects, cholesterol is one of the membrane components in cells and a precursor of ecdysteroid biosynthesis. Because insects lack two key enzymes, squalene synthase and lanosterol synthase, in the cholesterol biosynthesis pathway, they cannot autonomously synthesize cholesterol de novo from simple compounds and therefore have to obtain sterols from their diet. Sterol carrier protein (SCP) is a cholesterol-binding protein responsible for cholesterol absorption and transport.ResultsIn this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
6
12
0
Order By: Relevance
“…7 ), which indicated that F53 was an important site involved in the hydrophobic interaction of HaSCP-2 with cholesterol and may be more critical for the ligand binding ability of HaSCP-2 than other sites. This is consistent with the finding in AeSCP-2 with the F32 (corresponding to F53 in HaSCP-2) mutation in mosquito and F53 mutation in SlSCP-2 site 30 31 . Different from AeSCP-2, Y51A mutations decreased the binding affinity of SCP-2 to NBD-cholesterol ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…7 ), which indicated that F53 was an important site involved in the hydrophobic interaction of HaSCP-2 with cholesterol and may be more critical for the ligand binding ability of HaSCP-2 than other sites. This is consistent with the finding in AeSCP-2 with the F32 (corresponding to F53 in HaSCP-2) mutation in mosquito and F53 mutation in SlSCP-2 site 30 31 . Different from AeSCP-2, Y51A mutations decreased the binding affinity of SCP-2 to NBD-cholesterol ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…7 and Table 5 ), which suggested that these amino acids may be the important functional sites involved in the intracellular hydrophobic interaction between HaSCP-2 and cholesterol. This was consistent with the mutation analysis in AeSCP-2 and SlSCP-2 30 31 . Especially, the mutation of F53W caused more decreasing in binding affinity than in the other mutations ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results suggest that the response of SCPx to cholesterol is complicated, and is perhaps tissue‐ and/or species‐specific. In S. litura , SlSCPx‐2 had high affinity to cholesterol and fatty acids (Zhang et al , ). Over‐expression of SlSCPx and SlSCPx‐2 increased cholesterol uptake into Spli‐221 cells from a sterol‐containing medium (Guo et al , ).…”
Section: Discussionmentioning
confidence: 99%